Discusión y reflexión sobre los estereotipos de género entre el alumnado de secundaria. Experiencia didáctica en un grupo de 3º de ESO - Romera Ciria , Magdalena; Eceiza Pedrosa , Idoia (Huarte de San Juan. Filología y Didáctica de la Lengua, 2017)
The present study focuses on the identification of gender stereotypes by high school students through the use of a teaching unit in which discussion and reflection is promoted. We analyzed discourse samples of 3rd-year ESO students from a public high school in Navarra. The results indicate that classical stereotyping remains strongly rooted in the discourse of these adolescents. They reproduce and consider valid sexist relationship models and reject other models outside the accepted behavior. However, through joint discussion and reflection they are able to identify other salient aspects of gender inequality. The study also shows that the joint discussion, but especially the individual reflection on these aspects, remain essential in education.